Manual de recetas culinarias de frijol (Phaseolus vulgaris L.) - Gálvez E., Guillermo E. (International Center for Tropical Agriculture, 1991)
Recipes are provided to prepare 166 different dishes based in beans (soups, salads, side dishes, main dishes, desserts, and cold drinks). (CIAT)